2000
DOI: 10.1038/sj.bjp.0703231
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular profile of the calcium sensitizer EMD 57033 in open‐chest anaesthetized pigs with regionally stunned myocardium

Abstract: 1 Ca 2+ sensitizers enhance systolic function, but may impair relaxation in vitro; these e ects may di er in stunned and normal myocardium. We therefore studied the e ect of EMD 57033 on systolic and diastolic function of normal and stunned porcine myocardium in vivo. 2 Myocardial stunning by 15 min coronary occlusion and 30 min reperfusion abolished systolic shortening (SS) (baseline 13+1%) and decreased end-systolic elastance (E es ) from 67+7 to 47+5 mmHg mm 71 (both P50.05). Maximum rate of fall of myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…This augmentation occurred to a substantially greater extent in transgenic hearts than in controls, suggesting a specific capacity of this agent to affect the underlying defect. Despite basal diastolic dysfunction in TnI- hearts, diastolic function was enhanced by EMD-57033, consistent with prior in vivo studies (5,37). These data support a particular utility of EMD-57033 (and potentially similar calcium sensitizers) to treat myocardial dysfunction associated with TnI-proteolytic fragmentation.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This augmentation occurred to a substantially greater extent in transgenic hearts than in controls, suggesting a specific capacity of this agent to affect the underlying defect. Despite basal diastolic dysfunction in TnI- hearts, diastolic function was enhanced by EMD-57033, consistent with prior in vivo studies (5,37). These data support a particular utility of EMD-57033 (and potentially similar calcium sensitizers) to treat myocardial dysfunction associated with TnI-proteolytic fragmentation.…”
Section: Discussionsupporting
confidence: 78%
“…In these models, and unlike the present data, EMD-57033 was similarly effective in augmenting systolic function in the pathological model, as it was in parallel studies of control muscles, regional ventricular segments, or whole hearts. Some studies of regional myocardial stunning in the pig have also found similar responses in control and depressed myocardium (5). However, the pathophysiology of stunning in the pig appears to principally relate to altered calcium transients, rather than myofilament defects (20).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been found to increase the Ca 2+ -sensitivity of both myofibrillar ATPase and force development by skinned muscle fibers [71,72]. In vivo studies have also demonstrated that EMD 57033 enhances cardiac contractile function without affecting Ca 2+ -homeostasis [73][74][75][76][77]. The myofibrillar Ca 2+ -sensitizing effect of EMD 57033 is stereo-specific.…”
Section: Emd 57033mentioning
confidence: 98%